Bacterial Sputum Culture Results with Moderate and Severity Covid-19 Patients in Pinere Room Arifin Achmad Hospital, Riau Province (Future Science, 2022)
SARS CoV-2 is a new type of coronavirus and infects respiratory tract. Covid-19 may occur secondary bacterial infection, notably in severe degrees. Secondary bacterial infections are generally associated with viral respiratory infections concurrently after the primary infection. Sputum examination is essential to diagnose the etiology of the disease. So far, there has not been much research on secondary bacterial infections in Covid-19 patients. This research is a descriptive retrospective study. The study was conducted on moderate and severe Covid-19 patients treated in the PINERE Room by looking at the results of bacterial sputum cultures in confirmed Covid-19 patients from the Clinical Pathology Laboratory of Arifin Achmad Hospital, Riau Province starting from August 2020 to July 2021. This study is for the results of bacterial sputum culture with secondary infection in moderate and severe Covid-19 patients. The purpose of this research to analyze the relationship between sputum culture results and severity and outcome in Covid-19 patients. Of the 204 samples of bacterial sputum culture, the results obtained were normal flora 42.16%, Klebsiella pneumonia 22.55%, no growth of bacteria 10.78%, Acinetobacter baumannii 6.37%, Staphylococcus aureus 5.39%, Pseudomonas aureginosa 3, 43%, Staphylococcus maltophilia, Escheria colli, Enterobacter clocae 2.45% each. Based on the morphology of Gram-negative bacteria, 41.1% more than Gram-positive 6.37%.